“CV”: Change of Identity in the history of an urban square - Eplényi, Anna (4D Journal of Landscape Architecture and Garden Art, 2007)
In the 23rd of October, 2006 we inaugurated a new-called old square of Budapest, the ex-Felvonulási tér (Pageant’s Square) became Ötvenhatosok tere (The Square of the ‘56’s). This antagonistic identity-change shows the stressful life of the place. In the article the history of this square has been introduced in an environmental psychological approach, how the consecutive ideologies of the 20th century changes people’s attitude to this artificial square of Budapest. 150 years ago it was a part of Városliget, the capital’s biggest public park. which slowly became the territory of labour’s weekend activity, and demonstrations. In the ’30-es a church (Regnum Marianum) was built here as the sign of national conservative identity, which led to a different piacé identity. This intensified when the church was demolished for Stalin's enornious statue, where pageantries where held on the lst of May, 4th of April, 7th of November during the communist dictatorship. In 1956, people’s wrath cut down the huge statue. On this place is now the 50th year-anniversary monument of the Revolution. All this emotional, psychological and social process looks to get into balance now.
Keywords: The Square of the ‘56’s; Városliget; Rondó; Nebbien; Pageant’s Square; sculpture park; monument